Addressing the need for non-invasive lung assessment with time-resolved diffuse optics - Maffeis, Giulia; Serra, Nicola; Bossi, Alessandro; Avanzi, Elisabetta; Dalla Mora, Alberto; Di Sieno, Laura; Cubeddu, Rinaldo; Pifferi, Antonio; Taroni, Paola (Frontiers in Photonics, 2025)
Monitoring lungs functions is key for detecting several morbidities and pathologies. Photons in the 600–1,300 nm range might have the potential to reach lungs and provide compositional and functional information. Yet, few optical techniques have been challenged non-invasively so far. In this paper, we investigate the conditions to probe lungs using Time Domain Diffuse Optical Spectroscopy (TD-DOS). Counterintuitively, from Monte Carlo simulations we discovered that a higher absorption coefficient in the chest wall as compared to lungs increases sensitivity to deeper structures. In vivo measurements on the thorax of healthy volunteers during a forced breathing protocol, complemented with information on lung composition and previously evaluated in vivo spectra of porcine lung, suggest that this condition occurs above 1,100 nm. Multiple experimental setups were exploited to cover the 600–1,300 nm spectral range and test different source-detector distances (3–7 cm). All measurements exhibit oscillations consistent with the breathing rhythm, suggesting detection of lung expansion and compression. However, marked differences for different subjects and a complex dependence of the detected signal on the photon time-of-flight seem to allure to a non-trivial role of photon propagation through lungs, related–for instance–to the presence of alveoli and perhaps also to the overlying heterogeneous tissues. The unceasing development of time-resolved single-photon detectors with increasing performances above 1,000 nm, and a better understanding of lung optics–e.g., anomalous diffusion models–will help unravel the information from late, deep-travelling photons and lead to a novel photonic tool to probe the lungs non-invasively.